The Acquaintance Inference as Scalar Exhaustification - Kendrick, Jonathan Caleb (Proceedings of the Amsterdam Colloquium, 2025)
Predicates of personal taste (PPTs) trigger an inference that the speaker is acquainted with the thing being evaluated. While the acquaintance inference (AI) is often analyzed as part of an utterance’s non-at-issue content, we argue it’s best explained as a semantic entailment. Building on Magri’s [15, 16] analysis of individual-level predicates as obligatory triggers of scalar exhaustification, we show that, if we treat the AI as arising from obligatory scalar exhaustification, we can explain much of the relevant projection data, provided we are willing to treating the AI as a semantic entailment of PPTs.